2012
DOI: 10.1097/md.0b013e3182603598
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Microangiopathic Hemolytic Anemia

Abstract: Cancer-related microangiopathic hemolytic anemia (CR-MAHA) is a paraneoplastic syndrome characterized by Coombs-negative hemolytic anemia with schistocytes and thrombocytopenia. We reviewed and analyzed all cases of CR-MAHA reported since 1979 (the time of the last published review on this topic) according to predefined criteria. We found 154 cases associated with solid cancer and 14 with lymphoma. Among the solid cancers, gastric, breast, prostate, lung, and cancer of unknown primary (CUP) were most common; 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(121 citation statements)
references
References 121 publications
5
112
0
4
Order By: Relevance
“…Both of these differential diagnoses could explain the thrombocytopenia. CA-MAHA can be often confused with TTP, but the best distinguishing factor is that CA-MAHA is Coomb's negative, whereas TTP is positive [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Both of these differential diagnoses could explain the thrombocytopenia. CA-MAHA can be often confused with TTP, but the best distinguishing factor is that CA-MAHA is Coomb's negative, whereas TTP is positive [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Around 80% of patients with solid tumors have marrow infiltrated by cancer cells, and in one study, only 4 of 154 subjects had very low or absent ADAMTS-13 (a disintegrin and metalloproteinase with thrombospondin motifs, 13) activity. 18 In contrast, patients with lymphoma and myeloma with MAHA are much more likely to have significantly decreased ADAMTS-13 activity and thrombocytopenic thrombotic purpura. Treatment consists of cancer therapy when possible.…”
Section: Thrombocytosis and Thrombocytopeniamentioning
confidence: 94%
“…17 In addition, a recent article identified 168 cases of microangiopathic hemolytic anemia (MAHA) in a variety of cancers, and another review identified 34 cases of autoimmune hemolytic anemia associated with Hodgkin lymphoma. 18,19 Granulocytosis A 2009 review identified 758 patients with solid tumors and white blood cell count greater than 40,000/mL. 20 Only 10% were diagnosed with paraneoplastic granulocytosis.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Thrombotic microangiopathy (TMA), which some term cancer‐related microangiopathic hemolytic anemia (CR‐MAHA) 5, can be associated with multiple myeloma but is exceedingly rare, presents with thrombocytopenia, and is usually related to treatment with bortezomib 6. Our patient did not have thrombocytopenia, so this was lower on our differential.…”
Section: Introductionmentioning
confidence: 99%